Inovasi Program Lorong Sehat (Longset) Pada Dinas Kesehatan Kota Makassar - Syafruddin, Syafitri; Mone, Ansyari; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2021)
This research aims to analyze the Relative Advantage, Compatibility, Complexity, Triability, and Observability of Healthy Hallway innovation at the Health Office of Makassar City. This type of research is a qualitative description. The informants was 7 people. Data collection techniques in this study, namely observation, interviews, and documentation. The results of this study, the relative advantage that is owned is in addition to paying attention to the health hallway as well as the surrounding community with the suitability of the needs of the community, this innovation can be tested and implemented by the adopter's ease of observation. However, the complexity lies in the people who tend to be indifferent in implementing this innovation program, but the people in the surrounding environment help each other so that the complexity tends not to be felt.Keywords: Innovation, Healthy Hallway, Society.